(untitled) (Medico Legal Update, 2021)
The study was conducted from May -November 2019 among 114 dacryocystitis patients attending to ophthalmology department of Al-Yarmuk central hospital in Baghdad city. From of 114 patients with dacryocystitis, 90 (79%) patients had bacterial dacryocystitis, 24 (21%) with fungal dacryocystitis. According to the results 83(73%) recorded with chronic dacryocystitis and 31(27%) with acute dacryocystitis. The high percentage was bacterial dacryocystitis (32%), fungal dacryocystitis (38%) were at age of 74±0.3 y and the low percentage of bacterial was (11%) at 63±0.5 y and with fungal dacryocystitis (8%) at age of 42±0.3y. Patients with bacterial dacryocystitis had diabetes mellitus (56 %),arthritis and hypertension (28%,16 %) while the DM with fungal dacryocystitis (46%), arthritis, hypertension (38 %,16 %), S.aureus 23(26%), S.epidermidis 18 (20%),Streptococcus spp. 14 (16%), Pseudomonas spp. 11 (12%), E. coli 10 (11%), Enterobacter spp 9 (10%) finally Proteus spp. 5 (6%), while Aspergillus flavus represented 9 (37%) as causing fungal dacryocystitis, Aspergillus fumigates 7 (29%), Aspergillus niger 4 (17%)and Candida spp 4 (17%) . The antibiotic susceptibility tests revealed that S. aureus isolates were sensitive to Chloramphenicol (83%),. S.epidermidis isolates showed sensitivity to Gentamycin and Tetracycline (88%), Streptococcus spp showed the susceptibility to Erythromycin (93%), Ciprofloxacin (86%) respectively,Pseudomonas spp isolates considered highly sensitive to Tetracycline and Chloramphenicol (91%), E.coli isolates were also susceptible to Chloramphenicol (90%), Enterobacter spp were sensetive to Tetracycline and Gentamicin (78%),Proteus spp isolates seems sensitive to Chloramphenicol and Tetracycline (100%), Aspergillus spp. and Candida spp. isolates remain sensitive to Itraconazole, Voriconazole .